FACTORS INFLUENCING FINANCIAL STATEMENT INTEGRITY: A STUDY ON PROPERTY AND REAL ESTATE COMPANIES - Luh Pande Eka Setiawati; I Kadek Bagiana; Luh Putri Mas Mirayani (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
This study takes place from 2021–2024 to investigate the integrity of the financial statements of property and real estate companies listed on the IDX and how variables like good corporate governance (GCG), company size, and leverage affected it. The objective of this study is to investigate the relationships between conservative indexes for financial statement accuracy and institutional ownership, managerial ownership, independent commissioners, company size, and leverage. This research examines the impact of these variables on financial statement integrity using multiple linear regression analysis and a sample of 64 organizations. The results demonstrate that institutional ownership, managerial ownership, and independent commissioners positively affect the accuracy of financial statements, whereas business size and leverage have significant negative impacts. These results provide valuable insights into the role of corporate governance mechanisms and firm characteristics in enhancing the transparency and reliability of financial reporting in the real estate and property sector.